Physical-technical conditions, coaching and nutrition: An integrated approach to promote cohesion in sports team - Di Onofrio, V.; Montesano, P.; Mazzeo, F. (Journal of Human Sport & Exercise, 2019)
The aim was verified that the level of cohesion of a sports group is conditioned by numerous variables, which affect the athletes performance and lead to difficulties in adults relationships. The sample physical-technical and nutritional conditions and the help for the cohesion of a technique such as coaching were evaluated. Coaching can understand as the process in which individuals, mostly athletes, supported for their improvement and development in order to achieve performance high levels. 40 adults, aged between 35 and 45 years old, practicing football at amateur level for eight months, belonging to two different sports groups (blue and red group), have been observed. The results showed about 2.5% increase for blue group in Cooper test and about 1% in Sargent test, while for red group the improvement was approximately 1.5% in Cooper test and about 0.5% in Sargent test. 37 athletes correctly followed the nutrition specialists indications while 3 athletes showed negative responses. The personalized diets success confirmed by the decrease, in terms of kg, of the average percentage of athletes' body weight. All sample highlighted, with the answers to the 14 items of the questionnaire, significant percentage variations in lifestyles and relationships between group members.